Cochlear implantation in a patient with auditory neuropathy/dyssynchrony: A case report - (:unkn) unknown (MEDITERRANEAN SOC OTOLOGY & AUDIOLOGY, 2007)
Auditory neuropathy/dyssynchrony is a hearing disorder characterized by poor speech discrimination that is disproportionate to the degree of hearing loss, an abnormal or absent auditory brainstem response in the presence of normal otoacoustic emissions and cochlear microphonics, absent acoustic reflexes, absent efferent suppression of otoacoustic emissions, and abnormal masking level difference scores. In this study, the preoperative and postoperative audiologic test results of an adult patient with auditory neuropathy/dyssynchrony who underwent cochlear implantation are presented. Visually detected electrical stapedius reflexes and the results of neural response telemetry were noted intraoperatively. A statistically significant improvement in hearing and speech perception occurred after cochlear implantation. The results suggest that cochlear implantation can be performed to overcome dyssynchronization and enable rehabilitation.
Keywords: NEUROPATHY